Speech articulation disorder in patient using removable orthodontic appliance - Hofinessia, Dita; Rizali, Ervin; Syiarudin, Elih (Padjadjaran Journal of Dentistry, 2014)
Introduction: The physiologic of speech is a complex thing involving organ respiration, phonation, resonance, articulation and neurologic integration. The use of removable orthodontic appliance may cause speech articulation disorder and may affect patient’s speech function. The purpose of this research was to obtain an illustration of speech articulation disorder in patient using removable orthodontic appliance. Methods: This research was a descriptive research using the one group pretest posttest design. Speech articulation disorder was determined by testing the labiodental, linguoalveolar and linguopalatal consonants using the Goldman-Fristoe Test of Articulation test equipment. Results: Research result indicated that there was speech articulation disorder in the pronunciation of the consonants /f/; /v/; /t/; /d/; /r/; /s/; /j/; /g/; /k/ in the beginning of the word as many as 37%; 23%; 30%; 57%; 77%; 93%; 50%; 40%; 23%, in the middle of the word as many as 37%; 27%; 60%; 60%; 83%; 97%; 57%; 50%; 80% and in the end of the word as many as 17%; - ; 27%; 50%; 83%; 97%; - ; - ; 57% in the people using removable orthodontic appliance for the first time. Conclusion: Speech articulation disorders in patients with orthodontic removable appliance varies with the presentation of having most articulation disorders is in the pronunciation of consonants / s / in words.